Cooking fast and slow : easy, comforting, (mostly) plant-based recipes for busy people - Rudin, Natalia (Ten Speed Press, 2025)
A collection of over 100 simple, satisfying, plant-packed recipes that are low on effort but big on flavor, from Natalia Rudin, the viral creator behind Nat's Nourishments. Loved for her quick and delicious recipes whipped up after a long day as a personal chef, Natalia Rudin has created a show-stopping cookbook full of (mostly) plant-based recipes that are guaranteed to comfort, nourish, and delight. With chapters organized by timeframe that take less than 15 minutes, 30 minutes, or an hour; slower recipes to savor at the weekend or with friends; meal-prep ideas to elevate your packed lunches; breakfasts to be enjoyed slow or on the go; and treats to satisfy every sweet tooth, there is a recipe for every occasion. These recipes are short on ingredients but big on flavor and nutrition, with plenty of suggestions for additions and substitutions to suit what you eat and what you have available. Filled with silky sauces, sweet treats, and morning delights, Cooking Fast and Slow takes simple ingredients and elevates them so that every meal feels special and tastes incredible.